Bottom Incomes and the Measurement of Poverty: A Brief Assessment of the Literature - Lidia Ceriani; Vladimir Hlasny; Paolo Verme (Global Labor Organization (GLO), 2021)
The paper discusses the main issues related to negative and zero incomes that are relevant for the measurement of poverty. It shows the prevalence of non-positive incomes in high- and middle-income countries, provides an analysis of the sources and structure of these incomes, outlines the various approaches proposed by scholars and statistical agencies to treat non-positive incomes, and explains how non-positive incomes and alternative correction methods impact the measurement of standard poverty indexes. It is argued that negative and zero incomes cannot be treated equally in terms of household well-being and that standard methods used by practitioners fail to recognize this fact likely resulting in overestimations of poverty.
Keywords: D31; D63; I32; 330; Welfare measurement; Well-being; Poverty targeting; High- and middle-income countries; Survey non-response; Negative incomes; Zero incomes; Extreme income corrections